2006
DOI: 10.1271/bbb.60318
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Sphingoid Bases of Sea Cucumber Cerebrosides and Their Cytotoxicity against Human Colon Cancer Cells

Abstract: Sea cucumber is a health-beneficial food, and contains a variety of physiologically active substances including glycosphingolipids. We show here the sphingoid base composition of cerebrosides prepared from sea cucumber and the cytotoxicity against human colon cancer cell lines. The composition of sphingoid bases prepared from sea cucumber was different from that of mammals, and the major constituents estimated from mass spectra had a branched C17-19 alkyl chain with 1-3 double bonds. The viability of DLD-1, Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 36 publications
1
96
1
Order By: Relevance
“…29) Early in 1997, Kim et al have found that a cerebroside from Lycium chinense had beneficial effects against hepatocytes. 30) In the present study, we investigated the effects of AMC-2 on lipid metabolism in fatty liver rats.…”
Section: Discussionmentioning
confidence: 99%
“…29) Early in 1997, Kim et al have found that a cerebroside from Lycium chinense had beneficial effects against hepatocytes. 30) In the present study, we investigated the effects of AMC-2 on lipid metabolism in fatty liver rats.…”
Section: Discussionmentioning
confidence: 99%
“…Sugawara et al reported that sea cucumber Stichopus variegates sphingoid bases e.g. d17:1, 4, 8-sphingadienine d18:2 , d18:3 and d19:3 have strong cytotoxicity against some colon cancer cell lines via induction of apoptosis 16 . A novel identified glycosphingolipid, ophidiacerebroside C was isolated from Ophidiaster ophidiamus.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture of fatty acid methyl esters (FAMEs) obtained from methanolysis and a mixture of long chain aldehydes generated by periodate oxidation were simultaneously subjected to GC-MS, which revealed five FAME components ( [6][7][8] and the isomers with normal-, isoand anteiso-terminal methyl groups could be identified by the fragmentions M-15 for iso-, and M-29 for anteiso-, neither of which was detected in the mass spectra of normalLCAs. [9][10][11] Although the ratio of anteiso-type LCB was estimated to be 13.5%, the 13 C-NMR signals due to anteisoterminal methyl groups was not confirmed.…”
mentioning
confidence: 88%